PELAKSANAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CSR) DALAM PERSPEKTIF ISLAM - Fitra Rizal (IJoIS: Indonesian Journal of Islamic Studies, 2020)
This article aims to determine how corporate social responsibility (CSR) companies are in an Islamic perspective. The methodology used is qualitative using a descriptive-interpretative library research approach. The results show that CSR is a concept that organizations, especially companies, have a responsibility to consumers, employees, shareholders, communities and the environment in all aspects of company operations. Based on Islamic teachings, there is a greater concept related to CSR, which is one of the pillars of Islam regarding the expenditure of zakat. Through the collection of zakat, a prosperous society can be built. Even in Islamic economic instruments as a form of personal and social responsibility are ZIS instruments, namely Zakat, Infaq, and Shadaqah.